2019
DOI: 10.29029/busbed.490667
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Human Development and Economic Growth: An Application on Some African Countries

Abstract: ÖzBu çalışmada, Afrika kıtasında bulunan 52 ülke arasından verilerin elverişlilik durumuna göre seçilen 33 Afrika ülkesinin, 1995Afrika ülkesinin, -2014 yıllarına ait verilerinden yararlanılarak insani gelişme ile ekonomik büyüme arasındaki ilişki incelenmiştir. Çalışmamızda; insani gelişme endeksi bağımlı değişken, eğitim harcamaları, kişi başına düşen sağlık harcamaları ve GSYH ise bağımsız değişkenler olarak seçilmiştir. Analiz kısmında öncelikle serilerin yatay kesit bağımlılıkları incelenmiştir. Daha son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
1
2
0
2
Order By: Relevance
“…Unlike existing literature, this study, including GINI to the model, contributed to theliterature by determining the relationship between economic growth, human development and income distribution. Empirical results obtained are similar to those of Conceicao, et al (2009), Maqinand Sidharta (2017, Grubaugh (2015), Erdem andÇelik (2019), andRivera (2017).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Unlike existing literature, this study, including GINI to the model, contributed to theliterature by determining the relationship between economic growth, human development and income distribution. Empirical results obtained are similar to those of Conceicao, et al (2009), Maqinand Sidharta (2017, Grubaugh (2015), Erdem andÇelik (2019), andRivera (2017).…”
Section: Discussionsupporting
confidence: 87%
“…According to the findings of the study, there is a significant relationship between human development and economic growth. Erdem and Çelik (2019) analyzed the relationship between human development and growth by using the data of 33 countries in the African continent for the period 1995-2017 with the panel ARDL method. According to the findings of the analysis, a positive and significant relationship was found between human development and national income variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sağlık harcamaları bir ülkenin sağlık harcamaları, ekonomik büyümeyi doğrudan etkileyen harcamalar olarak değerlendirilir. Sağlık harcamaları bir maliyet türü olmayıp aynı zamanda yatırım harcamasıdır [18].…”
Section: Sağlık Göstergeleriunclassified
“…The same study concluded that there was a significant relationship between the variables in the long run, and both variables were positively related to each other. Erdem and Çelik (2019) analyzed the relationship between human development and economic growth with the ARDL method, using data from 33 African countries between the years 1995-2014. The results showed a positive effect between the income indices of human development index and economic growth in the short term, but an adverse effect between education and health indices and the economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%